2013
DOI: 10.1093/hmg/ddt183
|View full text |Cite
|
Sign up to set email alerts
|

Robust evidence for five new Graves' disease risk loci from a staged genome-wide association analysis

Abstract: Graves' disease (GD), characterized by autoantibodies targeting antigens specifically expressed in thyroid tissues causing hyperthyroidism, is triggered by a combination of genetic and environmental factors. However, only a few loci for GD risk were confirmed in the various ethnic groups, and additional genetic determinants have to be detected. In this study, we carried out a three-stage study in 9529 patients with GD and 9984 controls to identify new risk loci for GD and found genome-wide significant associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 56 publications
4
80
0
Order By: Relevance
“…In the past few years, studies using the strategy of candidate genes or genome-wide association studies (GWAS) have identified a few susceptibility loci for GD. The loci supported by solid evidence include HLA, CTLA4, TSHR, SCGB3A2, PTPN22 and FCRL3 (3,4,5,6,7), as well as seven new loci identified by our study group, RNASET2, GDCG4p14, GPR174-ITM2A, C1QTNF6-RAC2, SLAMF6, ABO and TG (8,9). RNASET2 and GDCG4p14 have been confirmed in the Caucasian GD cohorts (10,11).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…In the past few years, studies using the strategy of candidate genes or genome-wide association studies (GWAS) have identified a few susceptibility loci for GD. The loci supported by solid evidence include HLA, CTLA4, TSHR, SCGB3A2, PTPN22 and FCRL3 (3,4,5,6,7), as well as seven new loci identified by our study group, RNASET2, GDCG4p14, GPR174-ITM2A, C1QTNF6-RAC2, SLAMF6, ABO and TG (8,9). RNASET2 and GDCG4p14 have been confirmed in the Caucasian GD cohorts (10,11).…”
Section: Introductionsupporting
confidence: 67%
“…GD patients (1536) and 1516 sex-matched controls were recruited in the first stage, and an additional 3994 GD patients and 3510 sex-matched controls were recruited in the replication stage (8,9). Diagnosis of GD was based on documented clinical and biochemical evidence of GD, diffuse goiter, and the presence of at least one of the following: positive TRAb test, diffusely increased 131 I uptake in the thyroid gland, or exophthalmos (8,9). Graves' eye disease was classified into six grades according to the guidelines of the American Thyroid Association.…”
Section: Samples and Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The residue was column-chromatographed (n-hexane/ ethyl acetate/Et 3 N = 35:4:1) to yield 17 (704.1 mg, 1.516 mmol, 92%, yellow oil). In the purification with column chromatography, Et 3 Ndeactivated silica gel was used, that is, eluents containing 3% (v/v) Et 3 N. 1 = 169.61, 155.25, 155.16, 81.46, 81.31, 79.10, 79.05, 74.97, 74.89, 74.78, 63.67, 63.53, 63.26, 63.12, 55.26, 55.20, 55.13, 43.12, 43.06, 42.99, 42.93, 30.65, 30.62 3-Hydroxypropyl 3-(2-(Undecyloxy)phenyl)propanoate (18). To a solution of 1,3-propandiol (287.1 mg, 3.773 mmol), acid 15 (301.9 mg, 0.942 mmol), and DMAP (10.9 mg, 0.0907 mmol) in CH 2 Cl 2 (5 mL), EDCI (199.5 mg, 1.041 mmol) was added at 0°C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…If taken individually these genes seem to make a very modest contribution to disease predisposition, the fact that many of them participate in the regulation of the immune response has reinforced the evidence that GD is the consequence of a chronic adaptive immune response to selected thyroid antigens. The most promising GWAS detected genes associated with GD are listed in • ▶ Table 1 [10][11][12][13][14][15][16].…”
Section: Genetics Of Autoimmune Thyroid Diseases (Aitd)mentioning
confidence: 99%